2005
DOI: 10.1080/02640410500074391
|View full text |Cite
|
Sign up to set email alerts
|

Home advantage in the Australian football league

Abstract: The results of this study on home advantage in Australian rules football demonstrate that individual clubs have different home advantages. Traditional measures of home advantage as applied to whole competitions such as percentage of games won, and alternative measures such as average margin of victory for the home team, are calculated. Problems with these measures are discussed. Individual home advantages for each team are obtained using a linear model fitted to individual match margins; the resultant home adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 14 publications
(15 reference statements)
4
45
1
3
Order By: Relevance
“…These findings are consistent with those found previously in both rugby (Gómez et al, 2011;Morton, 2006) as well as other team sports (Nevill & Holder, 1999). Further elucidation of the mechanisms behind this phenomenon was beyond the scope of this investigation; however, previous (Clarke, 2005;Pollard, 2006), level of habituation to opposition facilities and conditions (Pollard, 2006) and sociological factors (Pollard, 2006) may explain this finding. Additionally, and not surprisingly, these results also emphasise both the relative and perceived strength of the opposition as an important consideration in determining the difficulty of a match.…”
Section: Discussionmentioning
confidence: 78%
“…These findings are consistent with those found previously in both rugby (Gómez et al, 2011;Morton, 2006) as well as other team sports (Nevill & Holder, 1999). Further elucidation of the mechanisms behind this phenomenon was beyond the scope of this investigation; however, previous (Clarke, 2005;Pollard, 2006), level of habituation to opposition facilities and conditions (Pollard, 2006) and sociological factors (Pollard, 2006) may explain this finding. Additionally, and not surprisingly, these results also emphasise both the relative and perceived strength of the opposition as an important consideration in determining the difficulty of a match.…”
Section: Discussionmentioning
confidence: 78%
“…This result was reinforced for professional basketball by Jones (2008) who finds team-specific home advantages in the National Basketball Association to lack statistical reliability. On the other hand, Clarke (2005) finds that home-team advantage varies systematically across teams in Australian football and believes it is due to differences in crowd effects. Jamieson (2010) addresses many aspects of home advantage, including variation over time.…”
Section: Review Of the Literaturementioning
confidence: 92%
“…Their success rate from betting on home teams during 1987-1995 was 58 percent, yet the return rate was negative; Bailey & Clarke (2004), who use data from 1997-2003 and present models predicting correctly up to 67 percent of winners, and producing betting profits of up to 15 percent;and Clarke (2005) who demonstrated that individual clubs have home ground advantages to different degrees, non-Victorian teams having a larger advantage. His results lend support to the conclusion that crowd effects are the main determinant of home ground advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Woodland & Woodland (2003), based on the fact that the proportion of underdog wins (beating the spread) in Gray & Gray (1997) and in Iskoe (1998) was 0.526 and 0.531, respectively, which is over half of their games, note that the reverse bias exists also in the National Football League (NFL) point spread market, yet there has been no empirical testing to support this finding. 5 See, for example, Schwartz & Barsky (1977) in baseball, football, ice hockey and college basketball; AmoakoAdu, Marmer & Yagil (1985) in the NFL; Golec & Tamarkin (1991) in the NFL and college football ;Courneya & Carron (1992), listing 16 studies in different sports; Holder & Nevill (1997) in tennis and golf; Vergin & Sosik (1999) in the NFL; Gandar, Zuber & Lamb (2001) in the NBA and MLB;and Clarke (2005) in the AFL.…”
Section: Discussionmentioning
confidence: 99%